Analyzing Inventory Turnover Performance in Different Retailing Mode of Operations - Junaid Ali Khan; Shiming Deng (European Scientific Journal, ESJ, 2016)
Inventory turnover differs across different retailers and operation modes employed by the retailers. Such a variation while undermining the usefulness of inventory turnover for performance analysis; requires particular attention. We perform an empirical analysis using sales data from a large retail firm for the year 2013-2016 for investigating the relationship of inventory turnover with mode of operations. The analysis reveals that the variation of inventory turnover among different mode of operations is much larger than variation of inventory turnover within each mode. So there is significant relationship between mode of operations and inventory turnover. This study inspects the influence of different channel structures on inventory turnover in a large supermarket, which has employed multiple modes of operations in different categories.